IMPLEMENTASI SISTEM PENDIDIKAN NON FORMAL SANTRIWATI YANG BERSEKOLAH MADRASAH ALIYAH DI PONDOK PESANTREN ANWARUL HALIMY SESELE LOMBOK BARAT - Sa'di, Kholisus; Fahmi, Agus; Purmadi, Ary (Universitas Pendidikan Mandalika, 2021)
Abstract: Abstract: Non-formal education is education that can be carried out in stages but is not official and the material is strengthening in formal educational institutions, such as educational units for courses, packages A, B, and C. Islamic non-formal education includes Islamic boarding schools. The focus of the problem is how to implement the non-formal education system for female students. The purpose of the study was to determine the implementation of the non-formal education system